Institution-Driven Comparative Advantage, Complex Goods and Organizational Choice - Shon Ferguson; Sara Formai (Research Institute of Industrial Economics (IFN), 2011)
The theory of the firm suggests that firms can respond to poor contract enforcement by vertically integrating their production process. The purpose of this paper is to examine whether firms' integration opportunities affect the way institutions determine international trade patterns. We find that vertical integration lessens the impact of a country's ability to enforce contracts on the comparative advantage of complex goods. We also find that countries with good financial institutions export disproportionately more in sectors that produce complex goods and that have a high propensity for vertical integration. In doing so we use a new outcome-based measure of vertical integration propensity and we employ several empirical strategies: cross section, panel and event study analysis. Our results confirm the role of institutions as source of comparative advantage and suggest that this depends not only on the technological characteristics of the goods produced but also on the way firms are able to organize the production process.
Keywords: D23; F10; F14; G20; G34; L22; L23; 330; International Trade; Comparative Advantage; Contract Enforcement; Financial Institutions; Vertical Integration; Vertikale Konzentration; Finanzmarkt; Institutionelle Infrastruktur; Produktionsorganisation; Komparativer Vorteil; Außenwirtschaftstheorie